End-to-End Quality of Service Over Heterogeneous Networks - Diaz, M. (Springer, 2017)
The book presents mechanisms, protocols, and system architectures to achieve end-to-end Quality-of-Service (QoS) over heterogeneous wired/wireless networks in the Internet. Particular focus is on measurement techniques, traffic engineering mechanisms and protocols, signalling protocols as well as transport protocol extensions to support fairness and QoS. It shows how those mechanisms and protocols can be combined into a comprehensive end-to-end QoS architecture to support QoS in the Internet over heterogeneous wired/wireless access networks. Finally, techniques for evaluation of QoS mechanisms such as simulation and emulation are presented.